Common bile duct exploration with choledochotomy and primary repair during pregnancy: Case Report - Jiaqi Chen; Liyong Zhang; Wenjuan Zhang; Zejin Zhao; Aijun Yu; Aijun Yu; Jian Li; Jian Li; Zhuqing Zhang; Zhuqing Zhang; Kai Chen; Kai Chen (Frontiers in Medicine)
We present a case of a woman in the second trimester of pregnancy who was admitted due to symptomatic common bile duct stones and gallstones. The patient underwent ultrasonography (US) and magnetic resonance cholangiopancreatography (MRCP) imaging, as well as a series of relevant blood tests, to establish a diagnosis. After a comprehensive assessment, simultaneous T-tube-free laparoscopic transcholedochal stone extraction and cholecystectomy were performed safely in the pregnant patient with common bile duct stones and gallstones. Postoperatively, the patient had an uneventful recovery. This case report aims to provide detailed information on the selection of treatment options for symptomatic choledocholithiasis combined with gallstones during pregnancy and to explore the feasibility and safety of performing concurrent T-tube-free laparoscopic choledochotomy for stone extraction in pregnant patients.